Economical design considerations for one-way 300 foot span, steel, parallel top & bottom chord warren trusses - Heath, Joshua (Kansas State University, 2012)
Trusses are an efficient way to span long distances with minimal material required. This report is a parametric study of the different design and construction aspects for a 300’-0” span, steel, Warren type truss. The study specifically examines the vertical loading on the truss, including components and cladding wind loading. The engineering variables investigated are panel point location, steel shape size and type, steel grade, member orientation, and connection design. Each of these aspects are studied independently with major results accounted for later in analysis. This allows for the most economical truss by reviewing each alternative possibly not commonly used in steel construction. However, trusses require special consideration in constructability compared to a common steel structure such as an office building. Because of this added complexity, constructability issues are also examined after all parametric studies are completed for engineering variables. Transportation regulations and restrictions, steel erecting (including the construction loading of the ASCE 37-02), and temporary structures are considered for the 300’-0” span steel truss. The results of the engineering design variables are documented showing the benefit of using W-Shape members with higher grades of steel in select members, and the rotation of members for truss stability and simplified connection detailing. Each of the multiple construction considerations are presented, providing the most recent information available at the time of this report.
Keywords: Trusses; Long span structures; Economics; Design considerations; Construction considerations; Steel; Architectural engineering (0462)